Centro de inclusión social y rehabilitación para habitantes de calle en la ciudad de Ibagué (Tolima), 2022 (2022)
Public space is the main source of life in cities, people live and move through it, in public spaces activities such as residence, recreation, sports, among others, are being affected for social reasons. In the present text, a theoretical, conceptual and practical analysis of different authors and actors with dif ferent perspectives will be carried out, which will serve as a fundamental basis for the approach and understanding of issues such as social construction, social relations, urban fabric, social insertion, Rehabilitation, among other concepts with the aim o to the improvement of the city. contributing